Regulation of energy prices in Russia - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2008)
Russia prices its energy commodities domestically much lower than the prices prevailing in the international market. Using a general equilibrium framework, we analyse reasons for why Russia should or should not use such a price regulation. First, being a major exporter of energy commodities and having considerable monopolistic market power, the country is able to use its supply in order to influence the international energy prices. A rational way to channel this rent to the domestic non-energy sector and to domestic consumers is through a lower, i.e., competitive, domestic price on energy than that in the world market. Second, we introduce the classic infant-industry argument with positive intertemporal spillovers through learning-by-doing linked to current production. These spillovers are likely to be relevant for manufacturing in a transition economy, which argument creates a further reason for a deviation in the pricing of energy to domestic industrial producers from the world market prices. However, an empirical consideration of these results and the estimation of the learningby-doing curve suggest that the first effect can in principle be sizeable, while the second is only marginal and that, overall, Russia is currently subsidising its domestic energy prices clearly too much. Further, we conclude that the country should not subsidise its domestic consumers more than its domestic industry, as it does in reality. We also derive the optimal domestic energy tax and show that it is modest in comparison to its current rate. The optimal pricing policy could therefore have a marked positive effect on the international supply of energy by Russia. – – Metsäalalla havaittiin perinteisen puunjalostuksen sivuvirtojen olevan merkittävin uutta arvonlisäystä synnyttävä sovellusalue metsäalan koko arvoketjussa. Tosin sellu- ja paperiteollisuuden liepeillä näyttää edelleen oleva voimakas halu tehostaa jalostusprosesseja, missä voitaisiin hyödyntää myös bioteknologioita. Kuitenkin metsäalan kohdalla erityisesti energiasovellusten tutkimus ja koulutus näyttää olevan tulevaisuuden ala. Lisäksi muilla teollisen biotekniikan aloilla on tarvetta jatkossa kehittää tutkimusta ja koulutusta. Bioteknologian perustutkintokoulutukseen sisältyy jo nykyisellään liiketoiminnan periaatteita ja kielenkäyttöä opettavia opintokokonaisuuksia; tätä toimintaa tulisi jatkaa ja mahdollisuuksien mukaan laajentaa. Akateemisen ”perustutkimuksen” ja kaupallistamiseen tähtäävän ”soveltavan tutkimuksen” luonne ja kannustimet ovat selkeästi erilaiset, vaikka biotekniikka-alan perustutkimus näyttää olevan monelta osin käyttötarkoituslähtöistä. Akateemisen tutkimuksen pääkannustimena ovat tieteelliset oivallukset ja tieteellinen julkaisutoiminta, ja käytännön sovellukset voivat olla hyvinkin kaukana tulevaisuudessa. Yhteiskuntamme haasteeksi muodostuu määrätietoisen ja fokusoidun kaupallistamiseen tähtäävän innovaatiotoiminnan tukeminen ja samanaikainen
Keywords: F13; F15; H23; 330; Energy; Russia; international and domestic prices; Energiepreispolitik; Russland